2016
DOI: 10.1186/s12874-016-0243-y
|View full text |Cite
|
Sign up to set email alerts
|

Abstracts reporting of HIV/AIDS randomized controlled trials in general medicine and infectious diseases journals: completeness to date and improvement in the quality since CONSORT extension for abstracts

Abstract: BackgroundSufficiently detailed abstracts of randomized controlled trials (RCTs) are important, because readers often base their assessment of a trial solely on information in the abstract. We aimed at comparing reporting quality of RCTs in HIV/AIDS medicine before and after the publication of the 2008 CONSORT extension for abstracts and to investigate factors associated with better reporting quality.MethodsWe searched PubMed/Medline for HIV/AIDS RCTs published between 2006–07 (Pre-CONSORT) and 2014–15 (Post-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
6
34
0
Order By: Relevance
“…The present study is, to our knowledge, the first study designed to compare the reporting quality of IMRaD and HS RCT abstracts. Among previous studies that used the CONSORT for Abstracts checklist to assess RCT abstract reporting, five have taken into account the structure of abstracts as a confounding variable [ 24 28 ]. In four of these studies, structure was analysed in two categories (unstructured vs. structured): 3 studies found that the reporting quality was significantly higher in structured abstracts, but not significantly higher anymore when other explanatory variables were accounted for [ 24 26 ]; while in the other study, authors found no significant difference between structured and unstructured abstracts in univariable analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study is, to our knowledge, the first study designed to compare the reporting quality of IMRaD and HS RCT abstracts. Among previous studies that used the CONSORT for Abstracts checklist to assess RCT abstract reporting, five have taken into account the structure of abstracts as a confounding variable [ 24 28 ]. In four of these studies, structure was analysed in two categories (unstructured vs. structured): 3 studies found that the reporting quality was significantly higher in structured abstracts, but not significantly higher anymore when other explanatory variables were accounted for [ 24 26 ]; while in the other study, authors found no significant difference between structured and unstructured abstracts in univariable analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In four of these studies, structure was analysed in two categories (unstructured vs. structured): 3 studies found that the reporting quality was significantly higher in structured abstracts, but not significantly higher anymore when other explanatory variables were accounted for [ 24 26 ]; while in the other study, authors found no significant difference between structured and unstructured abstracts in univariable analysis [ 27 ]. In a more recent study, Bigna et al [ 28 ] categorised abstract structure into IMRaD, 8-heading and ‘one-block’. They found that both IMRaD and 8-heading abstracts were significantly better reported than ‘one-block’ abstracts in univariable GEE analysis, and again the difference was not significant anymore when other covariates were adjusted for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work found improvement in some areas but still reported substandard adherence to CONSORT statement (5). Another investigation in the field of HIV/AIDS research reported a small improvement in some areas but a similar inconsistency in complying with the CONSORT recommendations (6). Both studies validated the continuing importance of consistent reporting of clinical trials in abstracts.…”
Section: Introductionmentioning
confidence: 58%
“…The proper evaluation of healthcare literature published prior to the existence of a relevant quality assessment tool creates an important opportunity to benchmark study quality over time by comparing recent reports with previous ones. This is critical to confirm if the quality assessment tool was actually able to promote an enhancement in the methodological and/or reporting process 10,19,20 .…”
Section: Main Textmentioning
confidence: 99%